THE EFFECT OF GPT CHAT ON THE LEARNING OUTCOMES OF KHAIRUN UNIVERSITY INFORMATICS STUDY PROGRAM STUDENTS - Albaar, Muhammad Ridha; Kapita, Syarifuddin N; Mamonto, Arifandy Mario (IJIS - Indonesian Journal On Information System, 2024)
In an era where technological innovation is increasingly penetrating all aspects of life, education cannot be separated from the positive impacts brought by technological progress. An interesting innovation that enriches the learning process is the use of ChatGPT (Generative Pre-trained Transformer). ChatGPT is an artificial intelligence language model that is capable of understanding and producing text with a high level of complexity. This research aims to examine the effect of ChatGPT and classroom learning on student learning outcomes. The research method used is quantitative. The results of this research consist of three hypotheses. 1. ChatGPT implementation has a positive relationship with student learning outcomes. Therefore, the hypothesis that states: "There is connectivity between the application of ChatGPT (X1) and learning outcomes (Y)" can be accepted. 2. Classroom learning has a positive relationship with student learning outcomes. Thus the hypothesis which states: "There is connectivity between learning in the classroom (X2) and learning outcomes (Y)" can be accepted. 3. The combination of implementing ChatGPT (X1) and classroom learning (X2) has a positive relationship to student learning outcomes (Y). Thus the hypothesis which states: "There is connectivity between the use of ChatGPT (X1) with classroom learning (X2) and learning outcomes (Y)" can be accepted.Keywords: ChatGpt, Class Learning, Learning Outcomes, Influence